The impact of energy efficiency on performance in service sector - Radojko Lukic (Economic and Environmental Studies (E&ES), 2016)
In this paper the emphasis is put on the specifics of energy efficiency impact on the profitability of the service sector, with special insight into trade. The theoretical and methodological presentations are illustrated by applying the comparative approach, on the original empirical data of the European Union and Serbia. To a certain extent, so as to thoroughly analyse the problem, we used the data from the surveys conducted in the United States of America, Canada and Russia. The results of empirical research show that energy efficiency in the service sector in Serbia is considerably lower than in the European Union and other countries with developed market economy. Given that, it is necessary to introduce appropriate measures to improve energy efficiency of the service sector in Serbia in the future. These are: modern energy technologies, increase of renewable energy share in total final energy consumption, reduction of energy consumption throughout the entire supply chain, reduction of carbon dioxide emissions related to the energy consumption, construction of energy efficient office buildings and retail facilities, and improvement of the existing. The ultimate effects of this are to improve profitability in the service sector in Serbia.
Keywords: Q40; Q44; Q32; Q57; 330; energy intensity; renewable energy sources; energy management; green energy; final energy consumption